Analysis Of E-Commerce Systems To Improve Sales Strategy Using Descriptive Methods In The Sarana Jaya Electronic Company - Lim, Albert; Wijaya, Eric; Hendra, Hendra; Mansyur, Reyhand Einstein; Sihombing, Oloan (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
E-commerce includes various activities such as sales, procurement, distribution and promotional transactions carried out via the Internet online network or electronic platforms. PT. Sarana Jaya Elektronik is a company that specializes in the distribution of electronic devices. Currently, PT. Sarana Jaya Elektronik has used an e-commerce system, namely the Tokopedia application, to sell its products. In order to find out the effect of implementing an e-commerce system on improving sales strategies, an analysis process can be carried out using descriptive methods. Descriptive research refers to a methodology in which researchers examine events and phenomena in the lives of individuals, encouraging one or a group of individuals to narrate their experiences.